Neutrophil to Lymphocyte Ratio Is Increased and Associated With Left Ventricular Diastolic Function in Newly Diagnosed Essential Hypertension Children - Hou, Miao; Cao, Lei; Ding, Yueyue; Chen, Ye; Wang, Bo; Shen, Jie; Zhou, Wanping; Huang, Jie; Xu, Qiuqin; Lv, Haitao; Sun, Ling (Frontiers in Pediatrics, 2021)
Aim Hypertension is associated with cardiac structural and functional changes, including left ventricular hypertrophy (LVH), LV systolic dysfunction diastolic dysfunction. Neutrophil to lymphocyte ratio (NLR) is a novel inflammatory biomarker associated with cardiovascular diseases. The current study aimed to evaluate NLR in children with newly diagnosed essential hypertension and its relationship between blood pressure and cardiac changes. Methods and subjects 65 children with newly diagnosed essential hypertension and 54 healthy children were included. Clinical characteristics, blood cell counts and biochemical parameters were collected. LVH was assessed by calculation of LV mass index (LVMI), and LV systolic function was evaluated by measuring LV ejection fraction and fractional shortening. LV diastolic function was primarily assessed with E/E’ ratio by doppler and echocardiography. Results The hypertension children had significantly higher LVMI and E/E’ ratio than the controls, whereas there was no difference in LV systolic function between the two groups. The NLR was significantly higher in the hypertension group than the control group. Moreover, NLR was positively correlated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) levels in the hypertension group. Additionally, a significantly positive correlation between NLR and E/E’ ratio was found in the hypertension group. However, NLR was not related to LVH and LV systolic function indicators in hypertension children. Conclusion NLR is elevated in hypertension children, and it is associated positively with office blood pressure levels. Moreover, NLR may help assess LV diastolic function in hypertension children.